Mathematics Anxiety and Mathematics Self Concept among Form Two Students in SM Sains Kuching - Mohamad Mahathir, Shamsulbahri (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study aims to identify mathematics anxiety level and type of mathematics self concept among form two students in SM Sains Kuching. Beside, this study interested to investigate whether a correlation exist between mathematics anxiety and mathematics self concept among the students. This study involved 104 of form two students in SM Sains Kuching. The instruments used in this study were 30 items of Mathematics Anxiety Rating Scale-Short version (MARSS) and ten items of Mathematics Self Description Questionnaire. The findings reveal that form two students in SM Sains Kuching have low level of mathematics anxiety (M=2.2202) and positive mathematics self concept (M=3.8683). The findings also found that there is no significant difference between male and female students in mathematics anxiety and mathematics self concept. However, female students indicated high score in mathematics anxiety (M=2.2771) compare to male students (M=2.1654). Female students also have low score in mathematics self concept (M=3.8245) compare to male students (M=3.9137). This study also found a negative correlation between mathematics anxiety and mathematics self concept among form two students in SM Sains Kuching which means that when the level of mathematics anxiety of the students is low, the mathematics self concept of the students will increase to positive.